Characterizing Changes in Screen Time During the COVID-19 Pandemic School Closures in Canada and Its Perceived Impact on Children With Autism Spectrum Disorder - Cardy, Robyn E.; Dupuis, Annie; Anagnostou, Evdokia; Ziolkowski, Justine; Biddiss, Elaine A.; Monga, Suneeta; Brian, Jessica; Penner, Melanie; Kushki, Azadeh (Frontiers in Psychiatry, 2021)
The COVID-19 pandemic has led to an increase in screen time for children and families. Traditionally, screen time has been associated with negative physical and mental health outcomes, and children with autism spectrum disorder (ASD) are at increased risk of these outcomes. The primary objectives of this study were to 1) characterize the change in screen time during COVID-19 school closures for children with ASD, and 2) examine the parent perceived impact of screen time on mental health and quality of life of children and their families. Canadian parents and caregivers of children 19 years of age and younger were eligible to participate in an anonymous, online survey study. This survey was available in English, consisted of 28 questions, took approximately 10-minutes to complete, and was available for six weeks (May 22 through July 6, 2020). The final sample consisted of 344 responses (ASD: n=127, mean age=11.7±4.06 years; community sample: n=287, mean age=9.4±4.26 years). There was a significant increase in screen time during the COVID-19 pandemic as compared to before the pandemic period in the ASD group (weekdays: mean difference=3.8 hours (95% CI 3.35-4.25), p<.0001; weekends: mean difference=1.5 hours (95% CI 1.17-1.92), p<.0001). Gender was a significant predictor of parent perceived mental health and quality of life, with male gender associated with a higher likelihood of negative impact (quality of life (child/family) OR=1.8 (95% CI 1.1-2.9), corrected p=.040; mental health OR=1.9 (95% CI 1.1-3.1), corrected p=.0028). Parents’ most frequently endorsed emotions towards screen time were guilt, frustration, and worry. Results of this survey study revealed that children with ASD were less likely to benefit from screen time to cope with social isolation, and screen time resulted in significantly more lost time on social interactions than the community sample, which may exacerbate difficulties in social domains. Given the unprecedented circumstances of the COVID-19 pandemic and the novel context of technology use, the findings of this study highlight the need for revision of screen time recommendations to reflect the current needs of children and families.